Giant aneurysm of distal posterior inferior cerebellar artery: a case report and review of the literature - Murrone, Domenico (BioMed Central, 2014)
INTRODUCTION: Aneurysms in the vertebrobasilar system are rare and in the distal segment of the posterior inferior cerebellar artery they are even less frequent. Giant aneurysms are also rare in the posterior cranial fossa. Giant aneurysms of the distal posterior inferior cerebellar artery generally can have mainly compressive effects on the adjacent structures and they can be mistaken for tumors. CASE PRESENTATION: We report the case of a 74-year-old Italian woman who presented with a complaint of dizziness. Her dizziness was found to be a result of aneurysmal dilatation arising from the distal segment of the right posterior inferior cerebellar artery. A mid-line suboccipital craniotomy was performed, and the aneurysm was clipped without post-operative deficits and with improvement in the patient’s dizziness. In our present report, we also review the literature and discuss our case with regard to the clinical and radiological features and surgical procedure performed. CONCLUSION: To the best of our knowledge, few cases of this type of aneurysm have been described in the literature. Our patient had a good outcome after surgical treatment.